Snow white and the wicked problems of the west: a look at the lines between empirical description and normative prescription (2010)
This article discusses the relationship between the origins of the concept of post-normal science, its potential as a heuristic and the phenomenon of complex science entailed policy problems in late industrial societies (wicked problems of the West). Drawing on arguments presented in the early works of Funtowicz and Ravetz, it is proposed that there is a fundamentally empirical character to the post-normal science call for democratizing expertise, which serves as an antidote to late industrial poisoning of the fairy tale ideal (Snow White) of a clean divide between science and politics. Post-normal science extended-peer-review methodology is interpreted as a response to a crisis in the governance of science. Rather than viewing extended-peer-review processes as products of the post-normal science discourse, here the post-normal science discourse is understood to provide a heuristic lens through which existing complex science/society collaborations and conflicts can be better understood. Two different post-normal science situations—management of mega-contamination in Bitterfeld, Germany, and eviction of the Parakuiyo Maasai from the eastern wetlands of the Usangu plains of Tanzania—are presented and the implications of their de facto extended-peer-review structures are discussed, to illustrate this heuristic potential.